PENERAPAN K3 BAGI PENAMBANG PASIR DI ALIRAN SUNGAI NOELMINA KECAMATAN BATUPUTIH KABUPATEN TIMOR TENGAH SELATAN PROVINSI NTT - Rumbino, Yusuf; Banunaek, Noni (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
CV. Talenalain is a company that mines sand without using excavators, but uses human labor and has a workforce of 25 people aged between 15 and 60 years. The Community Education Method is applied to increase workers' awareness of using PPE (personal protective equipment), understanding work hazards and diseases arising from sand mining activities. The material presented by the executive was about the benefits of PPE, handling minor incidental accidents, technical identification of hazards and diseases in the work environment. Apart from that, 25 sets of PPE equipment (helmets, gloves, rubber shoes, nose cover) were provided, 1 set of first aid kit, 1 set of warning signs, and several books on OHS Mining. The results of the activities of the implementation of Occupational Health and Safety (OHS) in the company can increase mining production by 20%, discipline to use PPE increased by 80%, increase in income of workers increased by 30%. This shows that the improvement of the OHS system can increase overall company productivity